2002
DOI: 10.1046/j.1432-1033.2002.03178.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel complexes of mammalian translation elongation factor eEF1A·GDP with uncharged tRNA and aminoacyl‐tRNA synthetase

Abstract: Multimolecular complexes involving the eukaryotic elongation factor 1A (eEF1A) have been suggested to play an important role in the channeling (vectorial transfer) of tRNA during protein synthesis [Negrutskii, B.S. & El'skaya, A.V. (1998) Prog. Nucleic Acids Res. Mol. Biol. 60, 47–78]. Recently we have demonstrated that besides performing its canonical function of forming a ternary complex with GTP and aminoacyl‐tRNA, the mammalian eEF1A can produce a noncanonical ternary complex with GDP and uncharged tRNA [P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 34 publications
1
39
0
6
Order By: Relevance
“…In addition to the lack of specific tRNA recognition capabilities, channeling of aminoacyl-tRNAs is a well documented phenomenon (61,62), and it is unlikely that free-standing charged tRNAs are ever present in the cell and available for interaction with trans-editing domains such as YbaK. Thus, one mechanism that synthetase-like proteins may use to carry out their specific functions in the cell, involves interaction with protein-tRNA complexes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the lack of specific tRNA recognition capabilities, channeling of aminoacyl-tRNAs is a well documented phenomenon (61,62), and it is unlikely that free-standing charged tRNAs are ever present in the cell and available for interaction with trans-editing domains such as YbaK. Thus, one mechanism that synthetase-like proteins may use to carry out their specific functions in the cell, involves interaction with protein-tRNA complexes.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, PhoAlaX and previously characterized trans-editing AlaXs (4) slightly deacylated cognate Ala-tRNA Ala when the concentration of the enzyme and temperature were increased (data not shown). Moreover, it has been shown that charged tRNAs are channeled from aaRSs to ribosomes without releasing free charged tRNAs (28,29). Therefore, the editing should collaborate with aminoacylation, and it is likely that duplication of the editing activities by the free-standing domains is not necessary for the ordinary translation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…While the ternary complex from bacteria is very well-characterized from a biochemical (11, 16 -18) as well as a structural (19,20) point of view, the available information about the corresponding eukaryotic eEF1A⅐GTP⅐aa-tRNA complex is more sparse and divergent. Notably, the existence of non-canonical mammalian eEF1A⅐GDP complexes with deacylated tRNA was suggested (21). The equilibrium dissociation constant, K d , of the latter complex was estimated to 20 nM (21), a value which is comparable to that of canonical EF-Tu⅐GTP⅐aa-tRNA, and 1000 times lower than the K d of the EF-Tu⅐GDP⅐aa-tRNA complex (16).…”
Section: ؊1 Smentioning
confidence: 99%